Yeats and/or Eliot: The Choice? - Mcdonald, D (Agenda Editions, 2017)
Several decades ago, when I was doing the things you then had to do in order to obtain a degree in English Literature, my contemporaries and I were offered a number of options within one of our compulsory examinations. The paper had originally (I think) been called ‘Special Poets’, though it was soon to change into ‘Special Authors’ (the better, presumably, to accommodate candidates shy of tackling verse); in my time, it had very recently undergone a perhaps more important change, by ceasing to require the study of a selected pair of poets – now, instead of (say) Wordsworth and Coleridge, Milton and Spenser, or Tennyson and Browning, one could devote oneself, if one chose, to a single one of the named (and, I need hardly say, exclusively male) list. The pairing which had just been decoupled in this way, and to which I devoted my poor attention all those years ago, was ‘W.B. Yeats and/or T.S. Eliot’: offered the choice between them (and I could still, as I remember, have chosen to study them in tandem), I opted for Yeats. This sounds like the most trivial of anecdotes, not to mention the most vain, and I give it here with a due sense of its slightness in the bigger scheme of things. But the choice itself, between Yeats and Eliot, which that undergraduate curriculum had incorporated, in its own minor and relatively unimportant way, was one that had – and, I think, still has – a proper critical bearing. Here, I want to venture as cautiously as I can into the different kinds of valuations and value-judgements – about the two poets, and about what poetry is (and is not) – that have gone into both comparisons between Yeats and Eliot and – just as significantly, in my view – the inability, the reluctance, or the failure to set the two writers in meaningful relation to one another.